Meningkatkan Kemampuan Mahasiswa dalam Mengidentifikasi Diphthong melalui Teknik Pengajaran Drim Berbasis Lesson Study - Deddy Sofyan; Mursidah Rahmah; Istiqlaliah Nurul Hidayati; Abdul Rosyid (FKIP UNIVERSITAS PAKUAN, 2016)
English Phonology is one of the subjects that is considered difficult to learn. Students assume that it is difficult since they have to memorize theories related to English pronunciation. To solve this problem, a team of lecturers agreed to apply a learning model called “DRIM” (dictating, reading, identifying, and modeling). The research was conducted within four cycles through Lesson Study program. The learning model consists of: 1) dictating, students listen to and write the sentences recited by the lecturer; 2) Reading, the students are given a text containing words with diphthongs. Those steps are done before the lecturer explains the material on diphthongs to diagnose students’ ability to recognize diphthongs; 3) Identifying, the students are asked to identify the given text and find words containing diphthongs After the students have understood the diphthongs and known how to pronounce them, the last step is 4) modeling. In modeling step, the students are asked to recite some words containing diphthongs and have other students repeat. By applying the model, the advantages that can be taken are as follows: a) giving more exercises and more various activities, b) improving listening skill, and c) growing students’ self- confidence to give examples to their other classmates.